REDESAIN SEMINARI MENENGAH PASTOR MERAUKE (PENDEKATAN ARSITEKTUR MODERN TROPIS) - Anton Topan; Henry Soleman Raubaba; Gregorius Ulahayanan (Faculty of Engineering, Musamus University, Merauke, Papua, Indonesia., 2018)
Pastor Bonus Middle Seminary, located in the YPPK Yos Sudarso High School complex in Merauke, currently does not have complete facilities in terms of space function and optimal building arrangement. Redesigning the Bonus Bonus Middle Seminary in Merauke is expected to be able to develop the existing seminary site area, so that it can meet the needs of facilities that are suitable for function and zoning. The purpose of this research is to redesign the Merauke Bonus Pastoral Seminary which prioritizes clarity of functions and zoning through a modern tropical architectural approach, as well as arranging building mass according to the site's shape by considering circulation. The method used in this study is the method of observation / direct observation to the location of the study, interviews with the seminary and Archdiocese of Merauke which provide direction for regional development and capacity building of seminary facilities. The results obtained are used as a reference for improving management facilities, educational facilities, talent talent facilities, religious facilities, residential facilities and service facilities. This design optimizes the lighting and natural airing of existing facilities by arranging the circulation and condition of the building against the tropical climate, so as to obtain a good design for the comfort of inner space and outside space. Kata-kunci: Redesign.,Seminary., Pastor Bonus., Merauke.